2009
DOI: 10.1177/0363546509350081
|View full text |Cite
|
Sign up to set email alerts
|

Retear Patterns after Arthroscopic Rotator Cuff Repair

Abstract: The suture bridge technique tended to better preserve the cuff tissue repaired to the insertion site of the rotator cuff than a single-row technique did; the retear in cases with a suture bridge technique was mainly in the musculotendinous junction. Direct retear at the footprint of the rotator cuff increased with severity of fatty degeneration or muscle atrophy in cases with a suture bridge technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(145 citation statements)
references
References 38 publications
6
135
2
2
Order By: Relevance
“…21,26 The high incidence of medial cuff failures after the medial-row knot in the conventional TOE repair demonstrates the necessity of taking preventive steps to increase the integrity at the medial row. 6,11 Because the medial row presents the load-bearing part and strangulation of the tendon may occur, modification of the conventional TOE technique by leaving the medial horizontal row untied may be necessary. We agree with Kim et al, 21 who concluded that the knotless double-row suture bridge repair might not only restore the rotator cuff footprint contact area but also reduce tension overload at the suture-tendon interface in the medial row, unlike the conventional TOE repair.…”
Section: Discussionmentioning
confidence: 99%
“…21,26 The high incidence of medial cuff failures after the medial-row knot in the conventional TOE repair demonstrates the necessity of taking preventive steps to increase the integrity at the medial row. 6,11 Because the medial row presents the load-bearing part and strangulation of the tendon may occur, modification of the conventional TOE technique by leaving the medial horizontal row untied may be necessary. We agree with Kim et al, 21 who concluded that the knotless double-row suture bridge repair might not only restore the rotator cuff footprint contact area but also reduce tension overload at the suture-tendon interface in the medial row, unlike the conventional TOE repair.…”
Section: Discussionmentioning
confidence: 99%
“…He noticed an unusual pattern of tendon failures at the musculotendinous junction of rotator cuffs repaired with this method. 15 Therefore, while there appears to be theoretical benefits to transosseous equivalent repairs, the significance of this medial failure is not yet known, and clearly needs to be addressed in future studies on this technique.…”
Section: Clinical Datamentioning
confidence: 99%
“…73,76 Despite improvements in our understanding of this disease process and advances in surgical treatment, healing after rotator cuff repair remains a significant clinical challenge. Repair failure rates of 20% to 70% continue to be reported, [15][16][17]22,45,46,71,72,84 depending on factors such as the patient's age, tear size and chronicity, muscle atrophy and degeneration, tendon quality, repair technique, and the postoperative rehabilitation. 14,16,23,37,42,58 Hence, there is a need for repair strategies that can augment the repair by mechanically reinforcing it, while at the same time biologically enhancing the intrinsic healing potential of the tendon.…”
mentioning
confidence: 99%